2007
DOI: 10.1590/s0104-14282007000200015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da aplicabilidade de técnicas MIC/FT-IR/DSC para a caracterização de filmes multicamadas

Abstract: Técnicas FT-IR de transmissão, reflexão atenuada (ATR), reflexão difusa (DRIFT), microscopia acoplada ao FT-IR (MIC/FT-IR) e detecção fotoacústica (PAS) foram utilizadas para a caracterização de filmes multicamadas. As técnicas ATR, MIC/FT-IR e PAS apresentaram os melhores resultados, provavelmente em função da possibilidade de análise somente da superfície das amostras com cristal (ATR), análise de cada camada da amostra separadamente (MIC/FT-IR) e possibilidade de variação da velocidade de obtenção do espect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Como a atividade dos microbicidas sugeriu a sua presença numa camada bem superficial da tinta, foi realizada a análise PAS, que, por suas características, já descritas, examina uma camada bem fina da superfície dos materiais, especialmente em maiores velocidades. Em função da velocidade 0,20 cm/s já ter apresentado bons resultados, em publicação recente do grupo [30] , foi adotada para esse estudo.…”
Section: Resultsunclassified
“…Como a atividade dos microbicidas sugeriu a sua presença numa camada bem superficial da tinta, foi realizada a análise PAS, que, por suas características, já descritas, examina uma camada bem fina da superfície dos materiais, especialmente em maiores velocidades. Em função da velocidade 0,20 cm/s já ter apresentado bons resultados, em publicação recente do grupo [30] , foi adotada para esse estudo.…”
Section: Resultsunclassified
“…Figure 4 shows the FTIR spectra of PPc, PPcr, and PPc/PPcr blends, non-aged and aged for 30 and 60 days, respectively. In the spectra of non-aged PPc and PPcr, the main PP bands were observed at 808 cm −1 , due to the angular deformation of the out-of-plane C-H; at 841 cm −1 and 1168 cm −1 ,corresponding to C-C isopropyl stretching; and at 974 and 1000 cm −1 , due to C-C stretching of CH 2 and CH 3 groups [27,28], respectively. The band at 1304 cm −1 corresponds to CH 2 vibrations; at 1375 and 1455 cm −1 , due to the symmetrical and asymmetrical angular deformations, respectively, of CH 3 [29,30].…”
Section: Fourier-transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…With the development of various polymers, there is also the need for the advancement of instrumental analysis techniques in order to determine the chemical structure of new materials and/or quantify them. As known, the FT-IR spectroscopy is one of the techniques that has merit for this purpose and has been successfully applied to various polymer systems in the group's laboratories of the Divisão de Química (AQI) of the Instituto de Aeronáutica e Espaço (IAE), including the use of last-edge techniques with surface analysis (universal attenuated total reflectance -UATR) in wide spectral range (mid-infrared, MIR, near-infrared, NIR, and others) [9][10][11] . The opportunity to develop a methodology applied to polymer blends, used in the automotive sector, is still not very explored; therefore, in the literature, FT-IR studies could be found for other types of materials for this sector, but not for the proposition of the present research.…”
Section: Introductionmentioning
confidence: 99%